If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4u + -1) + -12u = 11(2u + -6) Reorder the terms: (-1 + 4u) + -12u = 11(2u + -6) Remove parenthesis around (-1 + 4u) -1 + 4u + -12u = 11(2u + -6) Combine like terms: 4u + -12u = -8u -1 + -8u = 11(2u + -6) Reorder the terms: -1 + -8u = 11(-6 + 2u) -1 + -8u = (-6 * 11 + 2u * 11) -1 + -8u = (-66 + 22u) Solving -1 + -8u = -66 + 22u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-22u' to each side of the equation. -1 + -8u + -22u = -66 + 22u + -22u Combine like terms: -8u + -22u = -30u -1 + -30u = -66 + 22u + -22u Combine like terms: 22u + -22u = 0 -1 + -30u = -66 + 0 -1 + -30u = -66 Add '1' to each side of the equation. -1 + 1 + -30u = -66 + 1 Combine like terms: -1 + 1 = 0 0 + -30u = -66 + 1 -30u = -66 + 1 Combine like terms: -66 + 1 = -65 -30u = -65 Divide each side by '-30'. u = 2.166666667 Simplifying u = 2.166666667
| sinz=100findz | | F=39.99-x(.12) | | 3y+7=58 | | 6w-3w=6 | | 6=2y+41-3y | | 7x-9=-11 | | X+240y=124 | | 4x+7=5x-15 | | 7d-3-8d+15-d=-d-12+7d | | 12=2+-5w | | 78+17x-62-27x=-5x+46 | | 4a-3-6a-8=-3 | | Y-7=0(x-1) | | X+240y=74 | | Y+12=54 | | 4x+160y=96 | | 7x-(2x-9)+(3x+8)-(5x+6)=5 | | 6cos-3=0 | | 7x(2x-9)+(3x+8)-(5x+6)=5 | | -13=d+6 | | X+240y=50 | | 6.9/4=n/137 | | 4x+160y=80 | | x^4+10x^3+35x^2+52x+34=0 | | 6.1/5=n/148 | | x^4+10x+35x^2+52x+34=0 | | 267=5(8h+4)+7 | | 6x+10=3x+24 | | 6x+10=3x+34 | | x-9+3x=-5 | | 3/4r2-5/7r-2 | | 93+12y=3(4y-1)+96 |